2010
DOI: 10.5294/aqui.2010.10.1.6
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Cancer: Analysis of the Quality of a Program

Abstract: Objetivo: evaluar la calidad del Programa de detección temprana y control del cáncer de cuello uterino en una Unidad Prestadora de Servicios de Salud, de la Empresa Social del Estado Metrosalud, Medellín, Colombia, 2006-2008. Metodología: estudio descriptivo transversal. Se siguió el método de evaluación de programas de salud en los componentes problema, estructura, procesos y resultados propuesto por Avedis Donabediam, a partir de diferentes técnicas de recolección de información. Se hizo análisis estadístico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 8 publications
(2 reference statements)
0
2
0
1
Order By: Relevance
“…Fragmented healthcare networks operate through intricate administrative mechanisms, which impede an effective response in terms of cancer prevention [ 10 , 25 ]. This study was conducted in a low-income context and successfully identified these barriers, underscoring the necessity to implement system-level improvements to achieve greater integration of health services.…”
Section: Discussionmentioning
confidence: 99%
“…Fragmented healthcare networks operate through intricate administrative mechanisms, which impede an effective response in terms of cancer prevention [ 10 , 25 ]. This study was conducted in a low-income context and successfully identified these barriers, underscoring the necessity to implement system-level improvements to achieve greater integration of health services.…”
Section: Discussionmentioning
confidence: 99%
“…Another area in which failure was detected on knowledge of anatomy of the lower genital tract of women, specifically: the location of the endocervix, transformation zone, exocervix and, also unknown how cells are formed the transformation zone. Participants mentioned that they did not have training in the past year and those that had training only been theoretical and a few hours, also mentioned that there is no continuous monitoring of the program implementation of cervical cancer, at least in the seizure of Pap, which agrees with most of the countries in Latin America [15,16] where this health problem is very severe and does not have quality assurance systems that are external to official bodies.…”
Section: Discussionmentioning
confidence: 99%
“…7 Es un acontecimiento repetitivo de mutaciones de las células cancerígenas que producen un proceso de malignidad, el papiloma humano como enfermedad de transmisión sexual y los tipos 16, 18, 45, 31, 33, 52, 58 y 3528, de los cuales los tipos 16 y 18 están relacionados en mayor grado al desarrollo de cáncer de cuello uterino. 19…”
Section: Biología Del Cáncer De Cuello Uterinounclassified